2004
DOI: 10.1093/hmg/ddh194
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of common and specific genetic effects: association of the muscarinic acetylcholine receptor M2 (CHRM2) gene with alcohol dependence and major depressive syndrome

Abstract: Several correlated phenotypes, alcohol dependence, major depressive syndrome, and an endophenotype of electrophysiological measurements, event-related oscillations (EROs), have demonstrated linkage on the long arm of chromosome 7. Recently, we reported both linkage and association between polymorphisms in the gene encoding the muscarinic acetylcholine receptor M2 (CHRM2) and EROs. In this study, we evaluated whether genetic variation in the CHRM2 gene is also a risk factor for the correlated clinical character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
240
3

Year Published

2005
2005
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 286 publications
(252 citation statements)
references
References 47 publications
9
240
3
Order By: Relevance
“…Furthermore these identified genetic locations also have significant associations with the diagnoses of alcohol dependence Wang et al, 2004 ). In addition, recent studies suggested that GABRA2 is significantly associated with childhood conduct disorder symptoms as well as with marijuana dependence and illicit drug dependence ( Agrawal et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore these identified genetic locations also have significant associations with the diagnoses of alcohol dependence Wang et al, 2004 ). In addition, recent studies suggested that GABRA2 is significantly associated with childhood conduct disorder symptoms as well as with marijuana dependence and illicit drug dependence ( Agrawal et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Cannon et al (2006) reported that the distribution volume of the [ 18 F]FP-TZTP, a PET radioligand that is relatively selective for M2 receptors, was reduced in bipolar depressives relative to controls, although the sample size was too small to permit assessment of sex effects. In unipolar depression, Wang et al (2004) showed associations between genetic variation in the CHRM2 gene and depression arising in families with an alcohol-dependent proband, whereas Comings et al (2002) found that genetic variation in the 3 0 region of the CHRM2 gene (A/T 1890) was associated with MDD specifically in females. Taken together, these findings highlight the relevance of the muscarinic cholinergic system in depression and also appear complementary to the current report, as gender differences have been associated with both the genetic variation in the CHRM2 gene in MDD and now with the likelihood of experiencing an antidepressant response to scopolamine.…”
Section: Discussionmentioning
confidence: 99%
“…Those peaks harbor genes such as GABRA2, ADH (on chromosome 4) and CHRM2 and hTAS2R16 (on chromosome 7), which have subsequently found to be associated with risk for alcoholism Wang et al, 2004;Edenberg et al, 2006a;Hinrichs et al, 2006). We did not detect these peaks in our analyses.…”
Section: Discussionmentioning
confidence: 99%